Penampilan Fenotipik, Keragaman, dan Heritabilitas Sembilan Genotipe Teh [Camellia sinensis (L.) O. Kuntze] - Ilham Nur Ardhi Wicaksono; Budi Martono (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
The estimated value of genotype variability, phenotype variability, environmental variability, and heritability have an important role in breeding activities of tea in order to create the superior varieties. The objective of this study was to investigate the phenotypic performance, genotype and phenotype variation, and heritability value of nine genotypes of tea. The study was conducted at Pemandangan block, Tambi Plantation Unit, Wonosobo, Central Java, from April 2013 until April 2014. The Randomized Complete Block Design (RBD) with nine treatments and three replications was used in this study. The 9th of treatments consisted of 2 genotypes of tea resulting from a cross (GMB 3 and GMB 4), 2 introduced genotypes (TRI 2024 and TRI 2025), and 5 local genotypes resulting from selection (Cin 143, Kiara 8, RB 3, Tambi 1, and Tambi 2). The results showed that the genotype of GMB 3 more higher than other genotypes in pecco length, leaf length, leaf width, length of leaf stalk, and length of leaf internodes characters, whereas Tambi 2, GMB 3, and GMB 4 more higher in fresh weight of P+2 and P+3. The production of fresh shoot of GMB 4 more higher than the other genotypes, but not significant with GMB 3 and RB 3. The leaf length and fresh shoot production characters has a wide of genotype and phenotype variability, whereas the high of heritability value were found in all characters observed. The selection based on leaf length and fresh shoot production characters will be effective because both characters have a high genotypes variability and heritability.